Liquid Carbon-Boron Cluster Additives for Mixed Amine-50 - Xiaogang Mu; Shenghui Wang; Fanzhi Yang; Hao Li (Molecules)
Boron-containing compounds, known for their high calorific value, can significantly enhance the energy density of traditional liquid propellants. Through precise chemical modification of the C-H bonds in ortho-carborane, a novel liquid cluster material was synthesized: C,C′-Bis(2-ethylhexanoylmethyl)-o-carborane (BEHMC). This compound exhibits excellent stability, density, and energy properties. By combining BEHMC with mixed amine-50, a cluster liquid propellant was formulated, and its key performance metrics such as density, freezing point, mass calorific value, and volumetric calorific value were evaluated. The propellant achieved a density of 0.884 g·cm−3, a freezing point below −55 °C, a mass calorific value of 41.13 kJ·g−1, and a volumetric calorific value of 36.36 kJ·cm−3. The theoretical specific impulse reached 346 s, and the theoretical density impulse was 2.99 × 106 N·s·m−3. Compared to the traditional mixed amine-50/red fuming nitric acid propellant, the cluster liquid propellant developed in this study maintains a similar calorific value while improving the theoretical specific impulse and density impulse by 2.3% and 3.8%, respectively.